2013
DOI: 10.1002/j.0022-0337.2013.77.10.tb05604.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Atraumatic Restorative Treatment in U.S. Dental Schools: A Survey of Predoctoral Pediatric Dentistry Program Directors

Abstract: The International Dental Federation and World Health Organization have promoted the use of Atraumatic Restorative Treatment (ART) in modern clinical settings worldwide. In the United States, the practice of ART is not believed to be widely used, which may be a result of little attention given to ART training in predoctoral pediatric dentistry curricula in U.S. dental schools. This study investigated the extent of clinical and didactic instruction on ART provided in U.S. dental schools by surveying the predocto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Surveys of dental professionals have found that professional guidelines, or the lack thereof, are an important factor in selecting treatment modalities 28 – 30 . Even though SDF is only approved by the FDA for dentin hypersensitivity, the findings of our study showed that the most popular indications being taught for SDF were arresting caries in primary teeth and arresting root caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of dental professionals have found that professional guidelines, or the lack thereof, are an important factor in selecting treatment modalities 28 – 30 . Even though SDF is only approved by the FDA for dentin hypersensitivity, the findings of our study showed that the most popular indications being taught for SDF were arresting caries in primary teeth and arresting root caries.…”
Section: Discussionmentioning
confidence: 99%
“…This process often takes decades. Previous studies have shown that clinicians can take up to 15 years to substantially change the way they practice even when provided with sound information 24 , 27 , 28 , 33 , 34 . Moreover, new materials take years of research to gain a strong enough body of work to justify their addition to an evidence‐based dental curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…It was considered a “patient‐friendly” procedure . In addition to ART, an interim version of ART called the interim therapeutic restoration (ITR), which is almost identical to ART with the exception of proposed subsequent clinical intervention, can be provided prior to the definitive restoration . Finally, where resources allow, cavities in molars may be treated using the Hall technique.…”
Section: Prevention and Control Of Eccmentioning
confidence: 99%
“…Moreover, this technique can be performed in faster clinical sessions and with reduced cost of treatment being recommended by the International Dental Federation and World Health Organization in worldwide 16 . Researches showed that the longevity of ART restorations in primary teeth are similar from those produced using traditional methods using either amalgam or resin composite 17,18 .…”
Section: Discussionmentioning
confidence: 99%